Borehole temperature measurements at MeBo70 drill site GeoB23731-1, Caribbean Sea - Freudenthal, Tim (PANGAEA, 2024)
Borehole temperature measurements at site GeoB23731-1 were performed with the sea floor drill rig MARUM-MeBo70 during research expedition M154 in May 2019 southeast of the island of Montserrat in the Caribbean Sea. A platinum resistance sensor integrated in the 1343 Slimhole Memory Acoustic Tool developed by ANTARES Datasystems GmbH was used to measure the temperature of the fluid within the borehole with 103 mm diameter. The temperature range is –20 to +80 °C, the absolute accuracy within the limits of the measuring range is about 1 °C. The resolution of the temperature measurements is about 0.003 °C. Temperatures were logged with a frequency of 0.5 Hz by a memory adapter with an integrated clock that was synchronized with GPS-time. Borehole logging was conducted during trip out of the drill string. When the drilling operation was completed and the drill string was lifted by about 3.5 m the logging string was dropped into the drill string. After landing on the drill bit the logging string together with the drill string were tripped out of borehole. The depth control system of the drill rig was used to calculate the sensor depth with an accuracy of 0.1%.
Keywords: Borehole temperature; MeBo70